Political and Psychological Characteristics of Russian Governors in the Domestic Political Science: Review of Scientific Research - Matiusova, Anastasia I. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2021)
The article reviews the works of Russian researchers devoted to personal characteristics of Russian governors in terms of political and psychological approach. Drawing on the method of historical retrospection, the author distinguishes the transformation stages of the governorship institution since the 2000s, which required the revelation of different personal features in order for a governor to be successful. Theses transformation stages also led to changes in scientific approaches to the research of a governors psychological qualities. As a result, the author comes to the conclusion that current Russian political science fails to reflect the political and psychological portrait of modern Russian regional elite, including governors. The author notes that the personal characteristics of Russian governors are empirical indicators through which political scientists can evaluate the personality of a politician in the psychological sense, and, moreover, compare it with others, which proves the importance of this topic.